Governance, De-commoditization, and Communality among the Ngigua Leaders of San Marcos Tlacoyalco in Puebla, Mexico - López Varela, Guillermo; Manzano-Munguía, María Cristina (Ethnologies, 2021)
The Ngiguas, an Indigenous community of San Marcos Tlacoyalco in Puebla, Mexico, are in the process of building their governance through the design and practice of their own development projects on issues pertaining to the protection and exploitation of their natural resources, media autonomy, and traditional foods. Such a building effort is grounded on the concept of comunalidad (communality), which was expressed in non-patriarchal and non-capitalist terms by the late Mixe intellectual Floriberto Díaz Gómez in the 1980s. Since then, it has been used by the Ngigua people in their grassroots constructions of governance and development. Starting from the premise that development constitutes a Ngigua strategy for crafting communality, this article looks at how Ngigua leaders negotiate their governance and decommodification. Based on ethnographic research, this study presents communality as the spiral of intersubjective experiences of Indigenous people where the truth about the other is inhabited by Indigenous people in a non-linear dialogical perspective.